Coworker Support and OCB: Mediating Effects of Job Satisfaction and Motivation - Nelli Roza; Sumiati Sumiati; Suhelmi Helia; Afriyeni Afriyeni; Era Syafitri; Heriyandi Heriyandi (Journal of International Conference Proceedings, 2025)
This study looks at how colleague support affects Organisational Citizenship Behaviour (OCB) among nurses at RSUD Embung Fatimah, Batam, with an emphasis on the mediating functions of work motivation and job satisfaction.  With job satisfaction and motivation at work acting as mediators, the goal is to investigate the relationship between colleague support and OCB.  The study employed a quantitative methodology and an explanatory research design, with 146 nurses chosen by stratified random sampling.  SEM-PLS, or structural equation modeling-partial least squares, was used to analyse the data after it was gathered through the use of standardised questionnaires.  Job satisfaction strongly mediates the association between coworker support and OCB, according to the results, which also suggest that coworker support has a favourable impact on work motivation and job satisfaction.  However, OCB is neither directly impacted by nor mediates the relationship with job motivation.  In order to promote behaviours that increase organisational success, these findings highlight the need of establishing a supportive work environment.  To improve nurse service quality, hospital administration should concentrate on creating a collaborative culture